Trophic interactions in the "small pelagic fish - dolphins - fisheries" triangle: Outputs of a modelling approach in the North Aegean Sea (Eastern Mediterranean, Greece). (15th April 2021) - Tsagarakis, K.; Panigada, S.; Machias, A.; Giannoulaki, M.; Foutsi, A.; Pierantonio, N.; Paximadis, G.
Abstract: The aim of this work is to assess potential effects on dolphins caused by fishing Small Pelagic Fish (SPF) in the North Aegean Sea (Eastern Mediterranean, Greece) ecosystem due to competition for food. To this end, an existing Ecopath ecosystem model was updated with dolphins' abundance estimates derived from a recent dedicated aerial survey. The approach included the quantification of trophic impacts and the estimation of the fraction of production of SPF that is consumed by dolphins and their main competitor, the purse seine (PS) fishery. Overall, competition for resources (i.e., SPF) between purse seines and dolphins was at relatively low levels as revealed by the analyses of flows in the "small pelagic fish - dolphins - fisheries" triangle, despite the relatively high abundance of dolphins in the NAS compared to adjacent areas. Specifically, the consumption of anchovy's production by dolphins was very low (3.6%) while consumption by the PS fleet was almost four times higher (13.1%). A much larger fraction (71.8%) of consumption of anchovy's production was attributed to other predators. The competition for sardine was at slightly higher levels than for anchovy (4.6% consumption by dolphins and 20.4% removals by the PS fleet). Even when different SPF abundance estimates were assumed to take into account uncertainty and historical records from acoustic surveys, food competition didn't seem to be an important issue. Nevertheless, as anchovy (and to a lower extent sardine) was found to be a key forage species in the North Aegean Sea ecosystem according to two food web indices (SURF and Connectance indices) estimated, special attention should be placed to ensure that the dolphins' populations are not threatened by food depletion in the future. Graphical abstract: Image 1 Highlights: Food web model to explore trophic interactions of dolphins with fisheries. New dolphins estimates and historical small pelagic fish abundance considered. Low competition between purse seines and dolphins for small pelagic fish. Management of small pelagics should be priority for ecosystem approach.